2005
DOI: 10.1128/ec.4.8.1455-1464.2005
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of Histone H3 Lysine 36 Is Required for Normal Development in Neurospora crassa

Abstract: The SET domain is an evolutionarily conserved domain found predominantly in histone methyltransferases (HMTs). The Neurospora crassa genome includes nine SET domain genes (set-1 through set-9) in addition to dim-5, which encodes a histone H3 lysine 9 HMT required for DNA methylation. We demonstrate that Neurospora set-2 encodes a histone H3 lysine 36 (K36) methyltransferase and that it is essential for normal growth and development. We used repeat induced point mutation to make a set-2 mutant (set-2 RIP1 ) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 62 publications
4
81
1
Order By: Relevance
“…Obviously, frq is not the only gene that SET-2 directly regulated. In 2005, Adhvaryu et al have found that SET-2 is required for Neurospora growth and development (26), indicating that SET-2 regulate genes in these processes. Furthermore, previous study in Saccharomyces cerevisiae has shown that ϳ25% of the total genome displayed a significant increase of H4ac following deletion of Set-2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Obviously, frq is not the only gene that SET-2 directly regulated. In 2005, Adhvaryu et al have found that SET-2 is required for Neurospora growth and development (26), indicating that SET-2 regulate genes in these processes. Furthermore, previous study in Saccharomyces cerevisiae has shown that ϳ25% of the total genome displayed a significant increase of H4ac following deletion of Set-2.…”
Section: Discussionmentioning
confidence: 99%
“…After electrophoresis, proteins were transferred onto PVDF membrane, and Western blot analysis was performed. RNA was extracted as described previously and then analyzed by Northern blotting (26). For Northern blot analysis, equal amounts of total RNA (20 g) were loaded onto 1.3% agarose gels for electrophoresis, the RNAs were transferred to nylon membrane.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed ChIP-seq for H3K27me3 in set-1 and set-2 mutants, which are deficient for H3K4 and H3K36 methylation, respectively (Fig. S2) (70). We observed changes in the relative level of H3K27me3 enrichment in the set-2 strain at some Pc-target domains, but the global pattern of H3K27me3 was similar to wild type in both strains.…”
Section: H3k9me3 H3k27me3mentioning
confidence: 99%
“…Both Arabidopsis KYP and SUVH6 have a tyrosine at the switch position and are primarily monoMTases [57]. Neurospora crassa SET2 includes F296 at the switch position and the ezyme can add up to three methyl groups on histone H3 Lys-36 [58]. Chlamydomonas Set1 contains Y1768 at the switch position which would predict to generate mono-methylated Lys-4 on histone H3, an epigenetic mark for repressed euchromatin in Chlamydomonas [59].…”
Section: A Tyrosine/phenylalanine Switch Controls Product Specificitymentioning
confidence: 99%